2022
DOI: 10.1371/journal.pone.0278334
|View full text |Cite
|
Sign up to set email alerts
|

Post COVID-19 vaccination side effects and associated factors among vaccinated health care providers in Oromia region, Ethiopia in 2021

Abstract: Background Severe Acute Respiratory Syndrome (SARS COV-2) known as COVID-19 since its outbreak in 2019, more than 375 and 5.6 million were infected and dead, respectively. Its influence in all disciplines stimulated different industries to work day to night relentlessly to develop safe and effective vaccines to reduce the catastrophic effect of the disease. With the increasing number of people globally who have been vaccinated, the reports on possible adverse events have grown and gained great public attention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…For example, people not engaged in physical activity are more likely to develop side effects than those involved. The side effects were also more common among those who felt fear when vaccinated than those who did not [20]. Other studies have shown that females and those married are more likely to develop side effects than males and singles [21].…”
Section: Discussionmentioning
confidence: 89%
“…For example, people not engaged in physical activity are more likely to develop side effects than those involved. The side effects were also more common among those who felt fear when vaccinated than those who did not [20]. Other studies have shown that females and those married are more likely to develop side effects than males and singles [21].…”
Section: Discussionmentioning
confidence: 89%